1981
DOI: 10.1177/000456328101800306
|View full text |Cite
|
Sign up to set email alerts
|

Free-Radical Oxidation (Peroxidation) Products in Plasma in Normal and Abnormal Pregnancy

Abstract: SUMMARY Using recently developed methods for measuring free-radical oxidation products in biological material, plasma extracts were studied in 24 women in the first two trimesters of pregnancy, in 124 women in the third trimester of pregnancy, in 20 women with pre-eclamptic toxaemia (PET), and in a control group. There was a significant progressive rise of two groups of free-radical oxidation products throughout pregnancy and a significantly greater rise in PET. In women whose diastolic blood pressure rose to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
1
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(66 citation statements)
references
References 20 publications
7
57
1
1
Order By: Relevance
“…Their studies have also shown highly significant relation between a rising blood pressure and increasing free radical activity (6). Several investigations have hypothesized that the interaction between a disordered lipide profile, endothelin cell and oxidative stress is of major significance to the patho-physiology of preeclampsia (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies have also shown highly significant relation between a rising blood pressure and increasing free radical activity (6). Several investigations have hypothesized that the interaction between a disordered lipide profile, endothelin cell and oxidative stress is of major significance to the patho-physiology of preeclampsia (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Serum lipids increase significantly during pregnancy and are further elevated two fold during PIH (4,5,6). Several studies have shown that lipid peroxides like malondialdehyde (MDA) are significantly elevated in mild and severe PIH (7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Markers of lipid peroxidation i.e. MDA have been increased during the progression of normal pregnancy [29] . In our study we found that the MDA activity also increased in with normal and HIV pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The serum antioxidant may be consisting mainly of the elevated catalase activity. Although the significance of antioxidant activity noted in the pregnant serum remained to be elucidated yet, as free radical oxidation products increase in the blood during pregnancy (Wickens et al 1981), the antioxidant may be involved in their removal. There is a report describing the presence of peroxidase activity in the uterus and placenta, but the relation between the increased radical oxidation products in the serum and the peroxidase activity in the uterus and placenta remained to be clarified.…”
Section: Discussionmentioning
confidence: 99%